1867 Miss. Laws 412 - (:unkn) unknown (My University, 1867)
Ch. 317: Imposed property tax on several arms. Every pistol has more than one barrel or revolver, two dollars. On every single barrel pistol, one dollar. On each rifle, shotgun, army gun, fifty cents. On each and every Bowie-knife, sword-cane, or dirk, two dollars.
Keywords: TAX - PROPERTY OR SALES